Petits riens sophocléens : Antigone V: (v. 1095–1099, 1110–1112, 1113–1114, 1127–1130, 1140–1141 et 1149–1150, 1165–1171, 1206–1211, 1215–1218, 1223–1225, 1226–1230, 1251–1252, 1278–1280, 1344–1346) - Liberman, Gauthier (Hyperboreus, 2024)
This is the last of ﬁve sets of text-critical, exegetical and sometimes metrical remarks on Antigone. These *Sophocleuncula are not only minute philological notes but they involve broader issues having a bearing on the interpretation and meaning of the drama as a whole. These remarks were composed with a view to drawing attention to a number of forgotten or unseen diﬃculties and to trying to address a number of seen but unsolved problems more eﬃcaciously. The text and meaning of not a few other passages from other works of Sophocles or of other writers are also dealt with.